The Controversy of the Free Meal Programme in the General Election 2024 in Indonesia - Dama, Melati; Mayasari, Ayu Dewi; Situmorang, Lisbet (Citra Media Publishing, 2025)
The development of democracy in post-reform Indonesia shows dynamic conditions, including the widespread use of social policy as an electoral political tool. The controversy over this phenomenon is still rarely studied in depth in academic discourse. The 2024 general election in Indonesia is a clear example of the escalation of the use of social programmes as political instruments, a hallmark of post-reform democracy. This research focuses on the political construction and contestation of the Free Nutritious Meal (MBG) programme during the 2024 Presidential Election campaign. Using a descriptive qualitative approach and case study method, this research analyses how the MBG programme was produced, debated and disseminated through online media coverage during the official campaign period. The results showed two main findings. First, the MBG programme became a populist narrative that was strategically leveraged to increase the electability of candidates. Second, the programme generated widespread criticism from the public and civil society groups, highlighting the tendency of social policy instrumentality for electoral purposes. This research recommends the need for further studies to explore the long-term impact of social policy politicisation on public trust, democratic accountability, and the integrity of welfare distribution in Indonesia's evolving democracy.